Practical Considerations in Cooperative Therapeutic Trials - Freis, Edward D.; Williams, John H., Jr (Methods of Information in Medicine, 1962)
Various practical problems associated with cooperative therapeutic trials are discussed from the experience obtained during the U. S. Veterans Administration Cooperative Study on Antihypertensive Agents. The problems discussed include stratification of patients on the basis of severity, methods and precautions for achieving double-blind _ therapeutic regimens, methods for obtaining uniformity of data in different hospitals, and the need for inserting modifications in the protocol to take care of the patients developing life threatening complications.Other practical problems discussed include the need for obtaining the cooperation of the ward physicians and the problem associated with defaulters and those who do not follow the prescribed regimens. Experimental design helps to restrict errors introduced by variance between hospitals. Cooperative trials have goals and use methods which are somewhat different from the classical methods and aims of laboratory research, and should be evaluated in their proper frame of reference.Es werden verschiedene praktische Probleme besprochen, die bei kooperativen therapeutischen Prüfungen von Hochdruckpräparaten durch die U. S. Veterans Administration aufgetreten sind. Behandelt werden: Einteilung der Patienten nach dem Schweregrad der Krankheit, Zuverlässigkeit der Kriterien für die Beurteilung des Schweregrades, Vorsichtsmaßregeln zur Sicherung des doppelten Blindversuchs, Verfahren zur Wahrung einheitlicher Erhebungen in verschiedenen Kliniken und Hinweise in der Versuchsvorschrift für das Verhalten bei lebensbedrohlichen Komplikationen.Weiter werden besprochen: Die Notwendigkeit der Mitarbeit der Chefärzte, die Probleme, die durch ,,Bummelanten” und diejenigen auftreten, die sich nicht genau an die Versuchsvorschrift halten.